The job description and the marketing manager: An aid or a hindrance - R. Abratt (South African Journal of Business Management, 1983)
This paper explores the feasibility of applying a standard job description to the chief of the marketing department of the firm. This implies that the traditional job description theory may not be adequate for describing the job of the marketing manager or conversely, that marketing theory is not applied to job description. This paper discusses some aspects of job descriptions, the task of the marketing manager and then looks at the five actual job descriptions of marketing managers in five major companies in different industries. Conclusions are drawn from these findings.
Keywords: 650